Application of "Smart" Amine Donors for Rapid Screening and Scale‐Up of Transaminase‐Mediated Biotransformations. Issue 38 (20th August 2018) - Gomm, Andrew; Grigoriou, Stylianos; Peel, Christopher; Ryan, James; Mujtaba, Nafees; Clarke, Thomas; Kulcinskaja, Evelina; O'Reilly, Elaine
Abstract : The "smart" amine donors o ‐xylylenediamine and cadaverine were employed for the rapid screening of a large ketone library and subsequent preparative‐scale synthesis of selected compounds using a commercially available amine transaminase, ATA256. The methodology enables both screening and preparative‐scale biotransformations to be performed with a single enzyme and simplifies the generation of sp3‐rich small‐molecule libraries. Abstract : The "smart" amine donors o ‐xylylenediamine and cadaverine have been employed for the rapid screening of a large ketone library and subsequent preparative‐scale synthesis of a selection of optically pure chiral amines, using a commercially available amine transaminase biocatalyst.